Glutamate dehydrogenase: genetic mapping and isolation of regulatory mutants of Klebsiella aerogenes. - Bender, R A (1976)
The gene for glutamate dehydrogenase (gdhD) has been mapped in Klebsiella aerogenes by P1 transduction. It is linked to pyrF and trp with the order pyrF-trp-gdh. Complementation analysis using F' episomes from Escherichia coli suggests an analogous location in E. coli. Two mutants able to produce glutamate dehydrogenase in the presence of high levels of glutamine synthetase have been isolated. One, tightly linked to gdhD, shows normal repression control by glutamine synthetase but produces four times as much glutamate dehydrogenase activity as does the wild type under all conditions tested. The other revertant is not linked to gdhD or glnA.